Piperacillin/tazobactam treatment in children: evidence of subtherapeutic concentrations - Ye, Panpan; Shi, Jinyi; Guo, Zixuan; Yang, Xinmei; Li, Qian; Chen, Keguang; Zhao, Furong; Zhou, Haiyan; Zhang, Yehui; van den Anker, John; Song, Linlin; Zhao, Wei (Frontiers in Pharmacology, 2024)
Objective: Piperacillin/tazobactam (PIP/TAZ) is used for the treatment of lower respiratory tract bacterial infections in children. This study was performed to evaluate if the current dosing regimen results in therapeutic drug concentrations.Patients and methods: Patients suspected or proven lower respiratory tract bacterial infection and administrated PIP/TAZ intravenously for a duration of no less than 0.5 h, q6h-q12h daily were enrolled. Blood samples were collected and PIP concentrations were determined by high-performance liquid chromatography. The individual predicted concentration of PIP was evaluated using the individual empirical Bayesian estimates method. The evaluated PK/PD targets included: (1) 70% time when the predicted free drug concentration exceeds the minimum inhibitory concentration (fT > MIC) and (2) 50% fT > 4× MIC. Probability of target attainment (PTA) was assessed by the proportion of patients reached the PK/PD targets. The PIP concentrations between different groups of patients were compared.Results: A total of 57 samples were collected from 57 patients aged 2.26 (0.17 -12.58) years. For the PK/PD targets of 70% fT > MIC and 50% fT > 4× MIC for P.aeruginosa and K.pneumoniae, the PTA was all 0. The median Cmin of PIP was significantly higher in infants than in children, and the median Cmin after administration in q8h was significantly higher than that after administration in q12h.The current dose regimen of PIP/TAZ leads to extremely low plasma concentrations in most children with lower respiratory tract bacterial infections. More optimized dosing regimens or better alternative therapies need to be further explored.